2016
DOI: 10.1038/ncomms11276
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin-producing human mesenchymal cells target H19 lncRNA to augment endogenous progenitor function in hindlimb ischaemia

Abstract: Promoting the paracrine effects of human mesenchymal stem cell (hMSC) therapy may contribute to improvements in patient outcomes. Here we develop an innovative strategy to enhance the paracrine effects of hMSCs. In a mouse hindlimb ischaemia model, we examine the effects of hMSCs in which a novel triple-catalytic enzyme is introduced to stably produce prostacyclin (PGI2-hMSCs). We show that PGI2-hMSCs facilitate perfusion recovery and enhance running capability as compared with control hMSCs or iloprost (a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…38 However, others showed that alloUMSCs do not induce immune rejection 39 using immunodeficient animal models. 26,27 In the present study, we demonstrate that human UMSCs trigger immune rejection in wild-type C57BL mice with normal immune system. Our findings are more clinically relevant because most patients who require stem cell transplantation are immunocompetent.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…38 However, others showed that alloUMSCs do not induce immune rejection 39 using immunodeficient animal models. 26,27 In the present study, we demonstrate that human UMSCs trigger immune rejection in wild-type C57BL mice with normal immune system. Our findings are more clinically relevant because most patients who require stem cell transplantation are immunocompetent.…”
Section: Discussionsupporting
confidence: 58%
“…Perfusion was expressed as the perfusion ratio in the ischaemic leg compared with the contralateral, non-injured leg. 27 We focused our measurements on regional perfusion from ankle to toe because the extremities are most affected by ischaemic injury.…”
Section: Laser Doppler Perfusion Imagingmentioning
confidence: 99%
“…Therefore, a change in the distribution of PGH 2 to the particular isozyme is the key to control the metabolism of AA into the specific prostanoid. In recent years, using an enzymatic engineering approach to control the distribution of PGH 2 has been focused by our group to address this issue . In our previous studies, we have successfully created a single‐chain hybrid enzyme complex (SCHEC), COX‐1‐10aa‐PGIS, through the enzymatic engineering approach, which can force AA to be isomerized into PGI 2 , in order to rescue the deficiency of PGI 2 and to study the vascular protection effects of PGI 2 in cellular and animal models .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, using an enzymatic engineering approach to control the distribution of PGH 2 has been focused by our group to address this issue. [10][11][12][13][14][15][16][17] In our previous studies, we have successfully created a single-chain hybrid enzyme complex (SCHEC), COX-1-10aa-PGIS, through the enzymatic engineering approach, which can force AA to be isomerized into PGI 2 , in order to rescue the deficiency of PGI 2 and to study the vascular protection effects of PGI 2 in cellular and animal models. [10][11][12][13] Another SCHEC, COX-2-10aa-mPGES-1, which can effectively pass PGH 2 to mPGES-1, to convert AA to PGE 2 , has also been created as a model for understanding how PGE 2 is biosynthesized during inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation